Financial Management in Sericulture: A Study in Erode District of Tamil Nadu - Selvaraj, A. (Indian Journal of Finance, 2009)
Agriculture is the largest sector in many developing countries. Most of the developing countries have to depend much upon the development of agriculture for their economic development in order to meet the demand for food and agricultural raw-materials, earn foreign exchange for overhead investment and expansion of industries, stimulate industry expansion etc. Even in the case of developed countries, history reveals the importance of agriculture in the process of economic development. India is a predominantly peasant economy and agriculture forms the back bone of the Indian economy. Despite concerted industrialization in the recent past, agriculture continues to occupy a place of importance. All the other sector of the economy are also impacted by the performance of the agricultural sector.